Tradisi Nyadran Ditinjau Dalam Pendekatan Hermeneutik Study Islam - Edi Sulaiman; Muhtar Jamil; Muhammad Syaifullah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The Nyadran tradition is very important for the life and culture of Indonesian society. Nyadran carried out by people in Kubulangka village in Java is an activity that occurs every year before Eid or Ramadhan. Likewise, the nyadran tradition is one of the traditions that is still very well maintained in the people of Kubulangka Hamlet, Cukuh Balak sub-district, Tanggamus Regency. This research uses a qualitative descriptive method which involves direct observation in the field. The way we collect information for this research is by conducting interviews, observing and collecting documents. The main data is obtained directly from the person being interviewed or the object being researched. Secondary data comes from previous research such as journals and books related to the Nyadran Tradition. This data is used to explain the Nyadran Tradition in Javanese Culture through an Islamic studies approach in Kubulangka Village, Tanggamus. After that, the data is analyzed in a simplified manner, then displayed, and then conclusions are drawn. This tradition is usually carried out by the Kubulangka people every month of Ruwah in the Javanese calendar. Nyadran is a form of expression of gratitude and respect for ancestors who have passed away. Apart from being an expression of gratitude and respect for ancestors, Nyadran also has deep social and cultural meaning. Through this tradition, people can strengthen relationships between family members and between community members. Apart from that, Nyadran is also a means to strengthen the sense of togetherness and solidarity within the community.